Synthesis Optimation and Characterization of κ-Carrageenans from Eucheuma cottonii (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2023)
The objectives of the study are to determine the best condition for Eucheuma cottonii, obtained from Bantaeng regency, to produce κ-Carrageenan and to determine the characteristics of the carrageenan. Concentration of NaOH and KCl that are used to extract carrageenan, extraction time, and precipitation time are some variables that are measured for carrageenan extraction. After the best extraction condition is found, then the next step is characterization of the produced carrageenan. The best combination found to extract the highest amount of carrageenan are NaOH 4%, extraction time of 1 hour, KCl 6%, and precipitation time of 1 hour as well. For the characterization of ash, fiber, sulfate content, and viscosity are 2.24%; 0.65%; 0.35%; and 5 cP respectively.